Producción y comercialización de frutas deshidratadas como fuentes generadoras de ingreso para la parroquia rural Mariscal Sucre del cantón Milagro - León Icaza, Bolivar (2015)
This project was design as a source of income for the community of “Mariscal Sucre”, Canton Milagro through the production and marketing of dried fruits. Milagro is mainly characterized by the production of tropical fruits, being the principal activity thereof; however, this sector has been driven to the raw material is processed and converted into a product with added value. For that reason, It seeks to establish a company that can market the product within the canton Milagro and can expand to nearby counties; for this has developed a market research which has identified the factors that positively or negatively on the context in which the company will unfold. Everything is aligned with the guidelines established by the National Government as for the “Plan Nacional para el Buen Vivir” and transformation of the productive matrix……….